How Does Smoking Change the Clinicopathological Characteristics of Human Papillomavirus-Positive Oropharyngeal Squamous Cell Carcinoma? One Medical Center Experience. Issue 11 (August 2018) - Liu, Changxing; Talmor, Guy; Low, Garren MI; Wang, Tiffany V; Mann, Daljit S; Sinha, Uttam K; Kokot, Niels C
Introduction: Human papillomavirus (HPV)-positive and HPV-negative oropharyngeal squamous cell carcinomas (OPSCCs) are 2 distinct cancers, with HPV-positivity conferring a better prognosis. Smoking status is a complicating factor for both patient populations. There have been scattered literature that have reported on incomplete information regarding the profiles of their patient population. Details including age and sex distributions, TNM staging, histology grading, recurrence time and types, death rates, and the direct causes of deaths have been reported incompletely in the literature. Here, based on the experience at our university medical centers, we explored all the details of the important clinical profiles of HPV-negative OPSCC, HPV-positive OPSCC in smokers and nonsmokers. Objective: In this article, we compare detailed clinical profiles of HPV-negative OPSCC and HPV-positive OPSCC in both smokers and nonsmokers. The clinical profiles we elucidated here include patients' age and sex distribution, general health conditions, histology grading, TNM staging, perineural invasion (PNI), and lymphovascular invasion (LVI), extracapsular extension (ECE), recurrence rate and types, death rate, and direct causes. Specifically, we divided HPV-positive OPSCC into smokers and nonsmokers and compared the different clinical profiles between these groups to give a better idea of the complicating role of smoking in the development of HPV-positive OPSCC. Method: All patients with OPSCC at a tertiary care publicly funded county hospital and a tertiary care university hospital from June 2009-July 2015 were retrospectively reviewed. The attending physicians were the same at both hospitals. The primary outcome measure was posttreatment 2-year follow-up status (locoregional recurrence, distant recurrence, death rate). Other measures included HPV status based on p16 staining, smoking history, age, sex, comorbidities, tumor size, nodal and distant metastasis information, LVI, PNI, ECE, and tumor histology grade. Results: A total of 202 patients with OPSCC were identified. They were categorized into 3 groups: HPV-negative OPSCC group (HPV−), HPV-positive smoker group (HPV+SMK+), and HPV-positive nonsmoker group (HPV+SMK−). Patients of HPV− group are older (61.1 ± 11.6 years) than the other groups on average. The HPV− group has the highest percentage of women (22.7%). The HPV− patients with OPSCC have more comorbidities than the HPV+SMK+ group and the HPV+SMK− group, although there is no statistical difference. Grade 2 tumor is the most common histology grade for HPV− patients with OPSCC, whereas grade 3 is the most common grade for HPV+SMK+ and HPV+SMK− groups. Both PNI and LVI are positive at around 40% for all groups without any significant difference, but ECE is very common for HPV− OPSCC, at 86.7%, which is significantly higher than that of the HPV+SMK+ and HPV+SMK− groups. There was no difference of bilateral neck metastases noticed among different groups. For T staging and N staging, although HPV+SMK− and HPV+SMK+ patients have relatively lower T stages and higher N stages, there is no significant difference. HPV+SMK− group has highest TNM stages. All death rates and recurrence rates increase with time, but the death rate of HPV− group is about 4 times higher than that of the HPV+SMK+ group and 6 times higher than that of the HPV+SMK+ group. The major recurrence type of HPV− OPSCC and HPV+SMK+ is locoregional, and the major recurrence type of HPV+SMK+ is distant metastasis. Conclusions: Our data confirmed that HPV+ OPSCC normally presents with more advanced stage, however, it has better prognosis. In comparison, HPV− OPSCC presents at an earlier stage, but the prognosis is worse. Based on their clinical profiles, we noted that HPV-positive OPSCC cells are more "mobile"; they metastasize sooner and further. However, HPV-negative OPSCC cells are more locally infiltrative, leading to more locoregional recurrence. The HPV-positive patients usually are younger and healthier at diagnosis. Although HPV-positive OPSCC tend to be histologically higher grades, there was no statistical difference noticed. Metastatic and recurrent patterns are very different between HPV-positive and HPV-negative patients, but the death rate of HPV-negative patients is way higher, and it is mainly due to locoregional recurrences, which is the major recurrence type for HPV-negative patients. Of our note, smoking is a complicating factor for HPV-positive OPSCC, and it makes the death rate, recurrence rate, histology grade, and TNM staging shift toward HPV-negative OPSCC. How smoking makes HPV-positive OPSCC behave more like OPSCC-negative OPSCC deserves more translational research for further elucidation.